OROLBO‘YI MINTAQASI AHOLISINING PSIXOLOGIK O‘ZIGA XOS XUSUSIYATLARI - Shamshetova, A.K. (SCIENCE and SOCIETY, 2023)
This scientific article examines the current environmental problems in the Aral Sea region. The issues of increasing complexity of social, economic, medical and humanitarian problems as a result of environmental problems in the Aral Sea region, as well as their impact on the psychological characteristics of the individual were covered. The need to study psychologically approach to environmental problems and the issues of the organization of types of psychological services to the population, the opinions and conclusions of scientists in scientific research are described.
Keywords: population of the Aral Sea region; environmental problems; psychological service; environmental consciousness; environmental motivation